Resource Colorectal Anastomoses - Rocha, Ricardo (2024)
Introduction: There are situations in which the colorectal surgeon finds serious issues related to colorectal anastomosis. Materials and methods: We have performed a narrative review of the literature regarding different surgical techniques purposed for difficult or complicated colorectal anastomosis. Results and discussion: Intraoperative problems and surgical complications often lead colorectal surgeons to difficult colorectal anastomosis, having to use surgical techniques as enhancing colonic mobilization, improving rectal stump exposure, as well as coloanal anastomosis and invaginated or delayed anastomosis. Conclusion: Colorectal surgeons should have the technical capability to solve difficulties related to complicated colorectal anastomosis.